From Screens to Social Skills: The Effect of TikTok on Elementary Students' Social Behavior - tpoi, beatris (JOSAR (Journal of Students Academic Research), 2025)
The effect of Tiktok use on students' social behavior. This research aims To find out the influence of the use of tiktok on the social behavior of grade V students of SD Kristen Rantepao 5. There is excessive use of tiktok and makes students less concentrated in the learning process that occurs at school. The results of this study are a source of knowledge and overcome the influence of the use of TikTok on the social behavior of grade V students of SD Kristen Rantepao 5. In this study, the researcher used a quantitative approach and a type of correlation research, with observational data collection techniques, interviews and questionnaires. The results of data analysis show that there is an influence of TikTok use on students' social behavior where students tend to be unwilling to accept other people's opinions, ignore friends when talking and have no desire to help each other, reduced time to interact directly, boredom and peer influence in the use of TikTok, difficulty distinguishing useful and unuseful content, activeness in creating and sharing content, changes in social values such as honesty and tolerance